Analytisches Design von Freiformoptiken für Punktlichtquellen - Domhardt, André (Spektrum der Lichttechnik / Karlsruher Institut für Technologie (KIT), Lichttechnisches Institut, 2013)
During the development process of nonimaging systems the geometrical modeling of optical surfaces plays a decisive role. The presented mathematical algorithm generates optical freeform surfaces in a direct, non-iterative, calculation according to the specifications given by the optical designer. The shown method is applicable in particular to systems with very small light sources, e.g. LEDs, laser diodes and gas discharge lamps.